Structure Optimization and Simulation of a Multi-link Type Lower Limb Rehabilitation Robot - Fan Zefeng; Li Juan; Li Weida; Sun Lining (Jixie chuandong)
For reducing labor costs and improving the effect of lower limb rehabilitation training,a new-type multi-link lower limb rehabilitation robot is designed.Based on the research of the biomechanics of human walking and the mapping relations of human joint trajectory,a new-type multi-link lower limb rehabilitation robot is presented,and the kinematics model of the robot is established and analyzed to get the hip and knee angle curve of the robot.Meanwhile,the influence of key structural parameter on the joint trajectory and the mapping relationship is analyzed.The evaluation index of joint trajectory and the reproducibility of mapping relationship is established.By using the MATLAB,the structure parameters of multi-link lower limb rehabilitation mechanism is optimized.According to the results,the structure parameters of the robot structure are revised.